2014
DOI: 10.1371/journal.pone.0110221
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Neurotoxin from Venom of the Spider, Brachypelma albopilosum

Abstract: Spiders have evolved highly selective toxins for insects. There are many insecticidal neurotoxins in spider venoms. Although a large amount of work has been done to focus on neurotoxicity of spider components, little information, which is related with effects of spider toxins on tumor cell proliferation and cytotoxicity, is available for Brachypelma albopilosum venom. In this work, a novel spider neurotoxin (brachyin) was identified and characterized from venoms of the spider, Brachypelma albopilosum. Brachyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The MTT assays indicated that both synthetic peptides were not cytotoxic on the HT-29, SHSY5Y, and MDAMB231 cell lines up to 10 µM concentration. Similarly, no insecticidal effect was observed in Z. morio larvae 48 h after the injection of 300 µg peptide/kg body weight, a quantity much higher than those determining visible neurotoxic effects, or even death, for other invertebrate toxins ( Yang et al 2012 ; Zhong et al 2014 ). Finally, the antimicrobial activity assay evidenced that both MgCRP-I 7 and 9 did not show any effect on the selected bacterial and fungal strains at concentrations up to 32 µM.…”
Section: Resultsmentioning
confidence: 96%
“…The MTT assays indicated that both synthetic peptides were not cytotoxic on the HT-29, SHSY5Y, and MDAMB231 cell lines up to 10 µM concentration. Similarly, no insecticidal effect was observed in Z. morio larvae 48 h after the injection of 300 µg peptide/kg body weight, a quantity much higher than those determining visible neurotoxic effects, or even death, for other invertebrate toxins ( Yang et al 2012 ; Zhong et al 2014 ). Finally, the antimicrobial activity assay evidenced that both MgCRP-I 7 and 9 did not show any effect on the selected bacterial and fungal strains at concentrations up to 32 µM.…”
Section: Resultsmentioning
confidence: 96%
“…The described oedema activity [22] was not associated to a specific toxin since it was demonstrated to be induced by various pathways. Otherwise, the venoms of the Brachypelma genus have been widely studied, comprising insecticidal and neurotoxic activity [23,24], with small molecules related to tissue toxicity [25]. Despite scarce macromolecules, theraphosid spiders produce a wide range of peptides that can differ between species of the same genera and usually have selective ligand properties [26] that may also elicit inflammation and local reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Most spider venom contains multiple disulphide containing neurotoxins peptides which are pre-dominant component of venoms. A novel neurotoxin peptide was isolated from venom of the spider Brachypelma albopilosum having 10 kDa molecular weight (Yunhua et al, 2014). Venom toxins from spider result in paralysis of muscles or stroke, muscles weakness associated with arterial hypertension, cardiac arrhythmias, myocarditis or pulmonary edema (Del et al, 2013).…”
Section: International Journal Of Zoological Investigationsmentioning
confidence: 99%